Lignin-derived interconnected hierarchical porous carbon monolith with large areal/volumetric capacitances for supercapacitor. (April 2016) - Li, Hui; Yuan, Du; Tang, Chunhua; Wang, Suxi; Sun, Jiaotong; Li, Zibiao; Tang, Tao; Wang, Fuke; Gong, Hao; He, Chaobin
Abstract: A large scale 3D interconnected hierarchical porous carbon monolith was developed by a novel synthetic approach from the 2nd most abundant natural polymer, lignin. This newly derived carbon monolith possess desirable microstructure and high conductivity that enables the fabrication of a binder-/conductive additive-free thick electrode. The carbon monolith delivered simultaneously excellent areal/volumetric capacitances of 3.0 F cm −2 /97.1 F cm −3, at a high mass loading of 14.4 mg cm −2 . The areal capacitances obtained in our work are the highest among the reported carbon-based electrodes. The carbon monolith based symmetric supercapacitor achieved a high areal energy density of 0.16 mWh cm −2 at 1.75 mW cm −2, with excellent cycling performance (∼95% retention after 10, 000 cycles). Our work demonstrates the successful conversion of biomass waste into high-performance eletrode, and the promising areal/volumetric performances further suggest the developed approach may provide a positive route to improving the energy density of supercapacitor.